(untitled) (Al-Aasar, 2025)
Islam aspires to establish a welfare and peaceful society where every individual’s social, spiritual, and economic needs can be met, so that all the people living in the society can lead their lives with peace and security. Islam is a religion of social harmony that provides complete guidance on all issues concerning human life. In the present age, poverty, economic instability, and unemployment are issues that are increasing at an alarming rate. Poverty is not just a problem for Pakistan, but has now become an international issue. A large number of people are forced to live below the poverty line. A significant portion of society has been deprived of basic necessities of life. Economic instability itself is the cause of many evils, including inflation, begging, theft, delinquency, increased crime rates, depression, anxiety, and insecurity. The key causes of economic instability include usury, unjust distribution of wealth, poor planning, monopolization of national issues by specific groups, dishonesty, extravagance, and insecurity. Developed nations claim that they have introduced the best social security systems to eliminate poverty, but this claim is entirely contrary to the facts. The economic systems of the world have been practically tested in the past, and they have provided humanity with more problems than solutions. The demand of the present era is to find an immediate, simple, and practical solution to economic problems. Poverty, economic instability, lawlessness, unemployment, and similar deprivations can only be eradicated by the Islamic economic system, which is indeed the guarantor of sustainable economic development. Some key features of the Islamic economic system include the system of welfare (Kifalah), the establishment of Bayt al-Mal (public treasury), encouragement of charity and zakat, the payment of expiations (Kaffarat), moderation in income and spending, the concept of earning through halal (permissible) means, and the provision of Qard Hasan (benevolent loans). This research paper will discuss the various elements of the Islamic economic system and compare them with other economic systems, while also elaborating on its unique features.